PENULISAN PANTUN OLEH SISWA KELAS VII A SMP NEGERI 11 MUARO JAMBI TAHUN PELAJARAN 2013/2014 - Imaruddin ,; Yundi Fitrah; Yusra D (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2016)
ABSTRACT The purpose of this study is to describe the writing of poetry by students of class VII A of SMPN 11 Muaro Jambi under the terms of rhyme in the academic year 2013/2014. And the type of approach used in this research is quantitative descriptive. This research was conducted in SMP Negeri 11 Muaro in December 2013 and the instruments used in the study was the test. The research subjects are students of class VII A of SMPN 11 Muaro totaling 22 students. Data analysis performed in this study were: (1) Add up scores of individual students, (2) Summing overall score of students, (3) Mempersentasekan data. These results indicate that the writing of the poem by a student of class VII A of SMPN 11 Muaro Jambi 2013/2014 school year with a value of 4.54 included into the interval 4.5-5 with the criteria of very capable. From the results of data processing, the highest known percentage of each stanza consists of four rows of 100% category of highly capable, each line consists of 8-12 words amounted to 59.09% of highly skilled categories, elements of assessment requirements barsajak abab rhyme by 45.45% criteria very capable, first and second row is equal to 100% sampiran category of very capable and the third line and the fourth is the content of 95.45% category of very capable and the meaning of the content of the poem by 95.45% category of very capable. The results showed that the students of class VII A of SMPN 11 Muaro is very capable of writing poetry by the number of overall value of 4.54 in the interval from 4.5 to 5. Keywords: writing rhymes, students of class VII A SMPN 11 Muaro